Consequences of improper renovation decisions in a 17th century half-timbered building - Beata Nowogońska (Przegląd Naukowy Inżynieria i Kształtowanie Środowiska, 2020)

(untitled)
In the case of historic half-timbered buildings, the consequences of erroneous decisions regarding renovation or neglected conservation lead to irreversible damage processes. The effective undertaking of protection activities thus requires carrying out appropriate diagnostic studies. The results of these studies will make it possible to put forth renovation solutions which do not interfere with the historic architectural-structural layout of the building. The article presents the results of the assessment of the technical conditions of a 17th century church in Sękowice, built using traditional frame construction. As a consequence of earlier, inappropriate decisions pertaining to renovation works, a significant portion of the elements of the wooden construction underwent biological corrosion, as a result of which it lost its original mechanical properties. Some of the walls settled on corroded ground beams, with the uneven settling leading to distortions of the entire structure.